2020
DOI: 10.1088/2399-6528/ab5bb0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of the iron pnictide compound EuFe2As2 from first principles

Abstract: We report results of the electronic and mechanical structure properties of the iron pnictide compound EuFe 2 As 2 , at zero pressure. The open source computer code Quantum Espresso, which incorporates the Density Functional Theory (DFT), Pseudo Potentials (PP) and the Plane Wave (PW) were used to perform calculations from first principles. Projector-Augmented Wave (PAW) Pseudo Potentials were used in these calculations. The Density of States exhibits a sizeable superconducting gap and the band structure has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Structural optimization was done by doing a variable cell relaxation calculation and also optimizing K-points and cut-off energy. The lattice parameters of the tetragonal crystal structure were also calculated being guided by parameters from previous experimental studies on the compound and optimized to obtain a relaxed structure, [ 21 ], and the parameters are as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural optimization was done by doing a variable cell relaxation calculation and also optimizing K-points and cut-off energy. The lattice parameters of the tetragonal crystal structure were also calculated being guided by parameters from previous experimental studies on the compound and optimized to obtain a relaxed structure, [ 21 ], and the parameters are as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier studies, we reported the bulk, shear, and Young's modulus, and Poisson's ratio values of EuFe 2 As 2 at zero pressure; we tabulate these earlier results here for completeness [ 21 ] in Table 3 . Bulk, shear, and Young's modulus are obtained using the Voigt–Reuss–Hill approximation method.…”
Section: Resultsmentioning
confidence: 99%